2006
DOI: 10.12702/1984-7033.v06n01a07
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters in Mimosa scabrella populations by random and mixed reproduction models

Abstract: Estimates of genetic parameters in Mimosa scabrella populations by random and mixed reproduction models

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The mean coancestry coefficient within progenies (Θ = 0.162) was higher than expected in half-sib progenies (0.125). Thus, estimates of addictive genetic variance and heritability must be calculated using a relatedness coefficient (Sobierajski et al 2006) of 0.324 (2Θ) instead of 0.25. Knowledge about the coancestry coefficient is also important when estimating the variance effective size (N̂e), which was lower (N̂e = 2.76) than expected in the random mating populations (4, Furlani et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The mean coancestry coefficient within progenies (Θ = 0.162) was higher than expected in half-sib progenies (0.125). Thus, estimates of addictive genetic variance and heritability must be calculated using a relatedness coefficient (Sobierajski et al 2006) of 0.324 (2Θ) instead of 0.25. Knowledge about the coancestry coefficient is also important when estimating the variance effective size (N̂e), which was lower (N̂e = 2.76) than expected in the random mating populations (4, Furlani et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…In this way, over time the managed and the spontaneous bracatingais may be complementing each other genetically. At macro-geographical scales (up to 300 km), Sobierajski et al (2006b) also showed low genetic divergence (H p ) among populations of bracatinga. The similarity in diversity among all populations studied suggests the same genetic base, augmented by strong gene flow in past generations, and reveals that much of the genetic variability (95%) lies within the bracatingais, re-enforcing the role of local history in genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…After an environmental disturbance, this species develops favouring soil microorganisms due to the large deposition of litter and the symbiotic association with nitrogen-fixing bacteria, providing the environmental conditions for the growth of other secondary species in the initial steps of forest restoration (Citadini-Zanette et al 2017). Although this species does not depend on specialized pollinators (Sobierajski et al 2006), winter flowering may constrain the number of pollinators for a species commonly distributed in colder regions, such as the case of bracatinga. Despite the little information about its pollinators, the meliponids M. q. anthidioides and M. q. quadrifasciata were often cited as important visitors and pollinators of bracatinga (Catharino et al 1982; Ramalho et al 1989;Sobierajski et al 2006;Oliveira-Abreu et al 2014;Nascimento et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of M. scabrella with the stingless bees is well reported in the literature. Studies have demonstrated that M. q. quadrifasciata and M. q. anthidioides are important visitors feeding on nectar and pollen of bracatinga (Ramalho et al 1989;Sobierajski et al 2006;Oliveira-Abreu et al 2014;Nascimento et al 2015), besides being one of its pollinators (Catharino et al 1982).…”
Section: Introductionmentioning
confidence: 99%